Experimental and analytical investigations into wire electrochemical micro turning. Issue 1 (May 2019) - Tyagi, Aakash; Sharma, Vyom; Singh Patel, Divyansh; Jain, V. K.; Ramkumar, J.
Abstract: Electrochemical turning (ECT) has been studied by researchers for making axially symmetric parts of different materials by using shaped tools fed radially into the rotating workpiece. Despite having various advantages over other advanced machining processes, ECT has failed to gain much attention by the manufacturing industries and researchers because of the complexity involved in designing a shaped tool to give a desired shape and tolerances to the workpiece. In the present work, a systematic study is presented to understand the applicability of a microwire as a replacement for a shaped tool in this process. Simulations are carried out to understand the distribution of electric field lines and current density in case of wire electrochemical turning (ECT). The effects of insulting wire up to different angles on the evolved groove profile are investigated by performing simulation study. Minimum groove width is observed at the lowest value of 'tool exposed angle' (30°), while maximum groove depth is observed at the highest value of tool exposed angle (270°). In the later part of the work, an experimental study is performed to characterize a groove profile using a bare copper wire of diameter 200 µm. The effects of input parameters, such as workpiece rpm, tool radial insertion, applied potential and electrolyte concentration on responses like groove width, corner radius and taper angle are investigated. Finally, the understanding of behaviour of different process parameters is applied to perform operations like multi-step turning, microgroove turning and taper turning on copper and micro-threading on stainless steel 304.